Empowerment, climate change adaptation, and agricultural production: evidence from Niger - Wouterse, Fleur (International Food Policy Research Institute, 2017)
Presented by Fleur Wouterse (IFPRI), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.